Plasmonic Composite Films: Plasmonic‐Enhanced Cholesteric Films: Coassembling Anisotropic Gold Nanorods with Cellulose Nanocrystals (Advanced Optical Materials 9/2019). Issue 9 (3rd May 2019) - Cheng, Zheng; Ma, Yi; Yang, Lin; Cheng, Feng; Huang, Zhongjie; Natan, Avi; Li, Hongyan; Chen, Yong; Cao, Daxian; Huang, Zhifeng; Wang, YuHuang; Liu, Yongmin; et al.
Abstract : Hongli Zhu's Lab at Northeastern University (Boston, MA, USA) designed a free‐standing chiral plasmonic film by co‐assembling rod‐like cellulose nanocrystals (CNCs) and anisotropic plasmonic gold nanorods (GNRs), see article number1801816 by Hongli Zhu and co‐workers. The host–guest hybrid films exhibit tunable plasmonic optical properties including surface‐enhanced fluorescence and plasmon‐induced chiroptical activity. The interesting properties originate from the interaction of the photonic properties of the CNC matrix and plasmonic characteristics of GNRs. Incorporating photonic crystals with nanoplasmonic building blocks gives rise to novel optical properties that promise design of advanced multifunctional materials.